Strong adsorption of Al-doped carbon nanotubes toward cisplatin - Li, Wei; Li, Guo-Qing; Lu, Xiao-Min; Ma, Juan-Juan; Zeng, Peng-Yu; He, Qin-Yu; Wang, Yin-Zhen (Chemical physics letters, 2016)
The electron density map for 2e configuration cisplatin. The molecule can be strongly adsorbed onto Al-doped (7, 7) CNTs through its Pt atom. Al-doped CNTs is a kind of potential high quality delivery carrier for anticancer drug cisplatin. [Display omitted] •The cisplatin molecule can be strongly adsorbed onto the Al-doped (7, 7) CNTs through its Pt atom.•There is a certain relationship between adsorption energy and symmetry variation of Al-doped CNTs.•Al-doped CNTs is a kind of potential high quality delivery carrier for anticancer drug cisplatin. The adsorption of cisplatin molecule on Al-doped CNTs is investigated using density functional theory. The obtained results indicate that Al-doped carbon nanotubes can strongly absorb cisplatin. After absorbing cisplatin, the symmetry of CNTs has some changes. We innovatively defined a parameter of symmetry variation which relates to the adsorption. By analyzing the electronic structure, it can be concluded that under the circumstance that cisplatin was absorbed by Al-doped CNTs through aluminum atom of Al-doped CNTs. In conclusion, Al-doped CNTs is a kind of potential delivery carrier with high quality for anticancer drug cisplatin.